2016
DOI: 10.1080/09712119.2015.1129339
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gas production kinetics and digestibility of king grass (Pennisetum hybrid) added by organic mineral and natural crude tannin

Abstract: In vitro gas production kinetics and digestibility of king grass (Pennisetumhybrid) added by organic mineral and natural crude tannin,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Differences in grape processing could explain the variability in pomace activity due to the fact that content of different by-product compounds (pulp, granilla, stalk), are not always in the same proportions (Hixson et al, 2016) In line with our results, Atalay, 2020, also found differences for both gas and CH4 production after an incubation period of 24 h. In an in vitro fermentation study of dif-ferent grape varieties pomaces, Sofyan et al, 2017, also confirmed that the presence of tannins determines a decrease in gas production, but unlike our results, they find no differences in terms of CH4 production. Other authors such as Moate et al, 2014, demonstrated the reduction effect of grape by-products on CH4 production, by substi-tuting 36% of alfalfa hay with grape byproducts, obtaining a decrease between 20-24% of CH4 emissions in an in vivo study with cows.…”
Section: Discussionsupporting
confidence: 82%
“…Differences in grape processing could explain the variability in pomace activity due to the fact that content of different by-product compounds (pulp, granilla, stalk), are not always in the same proportions (Hixson et al, 2016) In line with our results, Atalay, 2020, also found differences for both gas and CH4 production after an incubation period of 24 h. In an in vitro fermentation study of dif-ferent grape varieties pomaces, Sofyan et al, 2017, also confirmed that the presence of tannins determines a decrease in gas production, but unlike our results, they find no differences in terms of CH4 production. Other authors such as Moate et al, 2014, demonstrated the reduction effect of grape by-products on CH4 production, by substi-tuting 36% of alfalfa hay with grape byproducts, obtaining a decrease between 20-24% of CH4 emissions in an in vivo study with cows.…”
Section: Discussionsupporting
confidence: 82%
“…RJ0 treatment (basal diet without SCS supplementation) gives the highest gas production than other treatment, while RJ4 (basal diet with 1% commercial chitosan supplementation) give lowest gas production. Gas production is the result of fermentation caused by the amount of microbial activity occurring in the rumen, as well as showing the amount of digested organic material [22]. The gas production kinetics continue to increase from hours 0 to 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Two syringes were filled with rumen-buffer only, samples were not inserted (blank). All of the syringes were blank, and samples were cultured in a 39°C incubator for 48 hours at random [22].…”
Section: Evaluation Of Fermentability and In Vitro Degradabilitymentioning
confidence: 99%
“…All syringes were placed in an incubator at random, and the samples and blank were kept at 39 °C for 48 hours. At 0, 1, 2, 4, 8, 10, 12, 18, 24, 36, and 48 h incubation times, the total amount of produced gas was observed (Sofyan et al 2017). Cumulative total gas production was fitted according to the Gompertz model (Machado et al 2014):…”
Section: In Vitro Ruminal Fermentationmentioning
confidence: 99%
“…To measure CH 4 , at 8 th and 24 th h into incubation a gas sample was collected during the in vitro gas production process. Methane from gas production was analysed using gas chromatography (Shimadzu GC14B, Shimadzu, Germany) completed with a Porapak N Column (50 °C) (Porapak N Column, Shimadzu, Germany) with helium (He) carrier gas at a flow rate of 60 ml/min and a flame ionization detector (150 °C), as described by Sofyan et al (2017).…”
Section: In Vitro Ruminal Fermentationmentioning
confidence: 99%